To Be Where You Are : Mitford Years #14 - Karon, Jan, 1937- (New York : G.P. Putnam's Sons, 2017)
"#1 New York Times bestselling author Jan Karon returns with the fourteenth novel in the beloved Mitford series, featuring three generations of Kavanaghs. After twelve years of wrestling with the conflicts of retirement, Father Tim Kavanagh realizes he doesn't need a steady job to prove himself. Then he's given one--but what, exactly, does it prove? Meanwhile, newly married Dooley and Lace face a crisis that empties their bank account and turns their household upside down. Is the honeymoon over? Is this where real life begins? As the Mitford Muse editor stumbles on a quick fix for marital woes and the town grocer falls in love for the first time, Father Tim and Cynthia receive an invitation to yet another family wedding. But perhaps the bottom line is this: While a star blinks out in the Mitford firmament, another soon blinks on at Meadowgate, and four-year-old Jack Tyler looks forward to the biggest day of his life--for now and forever. Jan Karon weaves together the everyday lives of two families, and the cast of characters that readers around the world now love like kin"--.
Keywords: Kavanagh, Timothy (Fictitious character) -- Fiction; Mitford (N.C. : Imaginary place) -- Fiction; Episcopalians -- Fiction; Clergy -- Fiction; Marriage -- Fiction; Weddings -- Fiction; FICTION / Family Life; FICTION / Christian / General; FICTION / Contemporary Women; Domestic fiction; Christian fiction